Modification of Sodium Lignosulfonate and Evaluation of its Potential Use as Detergent Builders. (4th March 2017) - Ou, Juhua; Zhao, Jianhong
Abstract : Sodium lignosulfonate (LS) was modified by polypropylene glycol diglycidyl ether (PPGDE) for the preparation of a surfactant (GLS), and firstly used for detergent builder. The effects of PPGDE content on the reaction and the properties of GLS were investigated. The structure of GLS was studied by Fourier transform infrared spectra (FTIR), ultraviolet spectrophotometer (UV), and gel permeation chromatography (GPC). The surface tension, critical micelle concentration (CMC), emulsifying ability, lime soap dispersing power (LSDP), and detergency were characterized. The results showed that GLS had higher surface activity and better emulsifying ability, LSDP, and detergency than that of LS. After decolorized by H2 O2, the whiteness retention value of decolorized LS on white cloth reached 91.9%, while that of decolorized GLS increased up to 99.4%. These results suggested that the decolorized GLS may provide a new perspective for detergent builders.